2003
DOI: 10.1002/bit.10664
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the external nitrification biological nutrient removal activated sludge (ENBNRAS) system

Abstract: A systematic lab-scale experimental investigation is reported for the external nitrification (EN) biological nutrient removal (BNR) activated sludge (ENBNRAS) system, which is a combined fixed and suspended medium system. The ENBNRAS system was proposed to intensify the treatment capacity of BNR-activated sludge (BNRAS) systems by addressing two difficulties often encountered in practice: (a) the long sludge age for nitrification requirement; and (b) sludge bulking. In the ENBNRAS system, nitrification is tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…Similar recoveries have been documented in the literature for BNR processes (Barker and Dold, 1995;Hu et al, 2003) with the ''missing'' COD being attributed to fermentation processes occurring in the anaerobic zone. Although direct evidence to support this hypothesis was not generated in the present study, the COD recovery improved during the higher rate operating conditions.…”
Section: Mass Balancessupporting
confidence: 69%
“…Similar recoveries have been documented in the literature for BNR processes (Barker and Dold, 1995;Hu et al, 2003) with the ''missing'' COD being attributed to fermentation processes occurring in the anaerobic zone. Although direct evidence to support this hypothesis was not generated in the present study, the COD recovery improved during the higher rate operating conditions.…”
Section: Mass Balancessupporting
confidence: 69%
“…The concept of biological phosphorus removal under anoxic conditions in municipal wastewater treatment, coupled by a fixed film nitrification which provided the nitrate for the anoxic zone, was applied by Bortone et al (1996), introducing for the first time the so-called "DEPHANOX" process. Other researchers based their investigation on this pattern (Hu et al 2003;Wang et al 2004a;Torrico et al 2008). Sludge recirculation also occurs for the nitrifying sludge (sludge II) from ST2 back to the nitrification tank.…”
Section: Competition For Organic Substrate Between Ordinarymentioning
confidence: 98%
“…Also Hu et al (2002b) indicated that the main factor affecting the occurrence of DPAOs and associated anoxic phosphate uptake was the nitrate load to the main anoxic reactor. The other potentially stimulating factors include the small aerobic mass fraction, sequence of reactors (nitrification and then denitrification) and reduced frequency of sludge alternation between the aerobic and anoxic states (Hu et al 2002b;Hu et al 2002c;Hu et al 2003a). The other potentially stimulating factors include the small aerobic mass fraction, sequence of reactors (nitrification and then denitrification) and reduced frequency of sludge alternation between the aerobic and anoxic states (Hu et al 2002b;Hu et al 2002c;Hu et al 2003a).…”
Section: Anoxic Growth Of Paomentioning
confidence: 99%